Impacto da implementação da qualidade na fase pré-analítica em um laboratório clínico prestador de serviço para o Sistema Único de Saúde - Pedreira, Samira Mariana Naciff (2017)
Objective: To evaluate the impact of the implementation of quality in the preanalytical phase in a clinical laboratory providing services for the Brazilian public healthcare system. Method: This study was carried out in three distinct stages. The first stage, before the intervention, was held between June and November 2015, summing up 7,058 consultations. The second stage or stage of interventions was carried out between December 2015 and May 2016. The interventions were carried out through permanent education actions to the professionals involved and implementation of standard operating procedures and forms (POPs, in Portuguese). After the interventions, the third stage began, evaluating the quality indicators in the first semester (between June and November 2016), in a total of 6,317 visits, and in the second semester after the interventions (between January and June 2017), in a total of 6,698 visits. The variables studied were the indicators of nonconformities of registry, nonconformities of collection, hemolysis and recollection and indicators of productivity of receptionists and phlebotomists. Stata 12® was used for statistical analysis. In order to verify the impact of the implementation of the quality, the Chi-square test was used, with a significance level of 5%, and Fisher's exact test. Results In the first semester after the interventions, a reduction of nonconformities related to the reception before the interventions was observed 9.7% after 7.4% (p <0.01) and to the collection before the intervention 1.0% after 0.4% (p <0.01) and increase in nonconformities related to screening before 0.7% after 1.2% (p = 0.003). However, there was no reduction in emissions at 5.1% (p <0.01), collection at 0.3% (p <0.01), and at 0.6% (p = 0.05) . In the first half of the year after the interventions, a significant increase of productivity of the reception desk before 36.4% after 39.30% (p<0.01) and of phlebotomists one before 21.5% after 34.8% and of the two before 14.2% and after 26.7% (p<0.01). In the second semester after the interventions the booth one maintained the productivity, the booth two increased before 31.2% after 6 months 38.4% and the booth three reduced before 32.4% after 6 months 24.7%. Phlebotomists increased productivity in relation to the period before interventions.. Conclusion: There was a positive impact in the implementation of the internal quality control in the preanalytical phase. After intervention, there was a decrease in nonconformities related to reception and collection and an increase of phlebotomist productivity. The reduction of nonconformities may reflect positively on the quality of the service provided to the patient.